2017
DOI: 10.4103/ijps.ijps_41_17
|View full text |Cite
|
Sign up to set email alerts
|

A study the various clinical and electrophysiological parameters of severity of carpal tunnel syndrome, their correlation with post-operative recovery

Abstract: Objective:We aimed to study the various clinical and electrophysiological parameters of severity of carpal tunnel syndrome (CTS) and to see if the severity of CTS affects recovery after surgery.Patients and Methods:A prospective study of 35 patients suffering from CTS. Clinical severity was assessed using visual analogue scale and standard questionnaires such as Levine and Disabilities of Arm, Shoulder and Hand questionnaires. All the patients underwent electrophysiological evaluation to assess electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…According to Nehete et al, the difference between pre operative and post-operative scores is a good indicator of post-operative recovery, but it does not show any correlation when compared with electrophysiological severity. 10 The study reconfirms the diagnostic role of NCV in CTS, but the electrophysiological severity does not always match the clinical severity. 10 Our study showed that there is no definitive relation between electrophysiological severity and clinical severity scores.…”
Section: Variable and Outcome Measuresmentioning
confidence: 74%
See 2 more Smart Citations
“…According to Nehete et al, the difference between pre operative and post-operative scores is a good indicator of post-operative recovery, but it does not show any correlation when compared with electrophysiological severity. 10 The study reconfirms the diagnostic role of NCV in CTS, but the electrophysiological severity does not always match the clinical severity. 10 Our study showed that there is no definitive relation between electrophysiological severity and clinical severity scores.…”
Section: Variable and Outcome Measuresmentioning
confidence: 74%
“…10 The study reconfirms the diagnostic role of NCV in CTS, but the electrophysiological severity does not always match the clinical severity. 10 Our study showed that there is no definitive relation between electrophysiological severity and clinical severity scores. In our study, we found the difference between preoperative and post-operative scores is a good indicator of post-operative recovery, but it does show a weak correlation when compared with electrophysiological severity.…”
Section: Variable and Outcome Measuresmentioning
confidence: 74%
See 1 more Smart Citation
“…This result is in favour of some other study results 14 . whereas some studies showed Carpal tunnel syndrome may be present in up to 42% in workers in certain occupations (e.g., poultry processing) and has annual incidence of 193 per 100,000 in all women 15 . Other high -risk occupations are computer professionals 16 , assembly line workers, concert pianists and construction workers with vibrating power tools 17 .…”
Section: Discussionmentioning
confidence: 98%
“…Although clinical severity scores have a diagnostic role in carpal tunnel syndrome, they do not correlate with recovery following carpal tunnel release. 3 Favorable results and high patient satisfaction have been reported for patients with severe disease undergoing carpal tunnel release. 4 We have recognized a subset of patients with severe disease who do not follow the typical, uneventful recovery pathway postoperatively.…”
mentioning
confidence: 99%